As paisagens nas pinturas de Ido Finotti: reflexões artísticas e históricas - Finotti, Ricardo Alves (2016)
This research studies the landscape paintings of the artist Ido Finotti, specifically the Brazilian cerrado vegetation and rivers landscape paintings, in the region of Triângulo Mineiro, mainly Uberlândia and the surrounding cities as Uberaba and Araguari. The artist produced the landscape paintings from 1947 to 1980. This study searches to understand the poetic in the paintings and identify the elements that the artist chose to create the visuality of landscape to build a regional identity. Therefore, it links the artistic and historical reflections with the general ideas about the landscape painting in the Universal History of Art and in the Brazilian History of Art through the main landscape painters. First, this work shows the trajectory of the artist Ido Finotti and the two phases of his paintings: as a decorative painter of walls from 1920 to 1940, then as an oil painter artist on canvas. Second, the national and foreign authors studied were from several fields: Visual Arts, History, History of the Art, Philosophy and Geography, but had produced literature on the idea and the subject of landscape in the painting. The initial reading was about some workmanships of Ido Finotti, which included 142 landscapes paintings; interviews; articles, periodicals and magazines collected; documents, brochures and catalogues gathered. The comparison between the written and visual sources made possible the textual construction of this research.